Factors Associated With Degree and Length of Recovery in Children With Mild and Complicated Mild Traumatic Brain Injury. Issue 5 (6th May 2019) - Gardner, James E; Teramoto, Masaru; Hansen, Colby
Abstract: BACKGROUND: A complicated mild traumatic brain injury (C-mTBI) is an mTBI with some form of intracranial abnormality identified radiographically. The lack of knowledge in recovery patterns and no clear guidelines on return to activity in children with C-mTBI provide unique challenges to physicians. OBJECTIVE: To examine recovery patterns among three cohorts: mTBI, mTBI with skull fracture only (mTBI-SF), and C-mTBI via a cross-sectional survey. METHODS: Caregivers of children with mTBI (from hospital database queries 2010–2013) were mailed a questionnaire on preinjury health, postinjury recovery, and activity patterns before and after injury. We examined degree (0-10 with 10 being complete recovery) and length (in months) of recovery in children with mTBI, and associations of potential risk factors to these variables. RESULTS: Of the 1777 surveyed, a total of 285 complete responses were analyzed for this study. Data included 175 (61.4%) children with mTBI, 33 (11.6%) children with mTBI-SF, and 77 (27.0%) children with C-mTBI. Older age and C-mTBI (vs mTBI) were significantly associated with a lower degree and longer period of recovery ( P  < .05). Predicted probabilities of complete recovery for children with mTBI, those with mTBI-SF, and those with C-mTBI were 65.5%, 52.7%, and 40.0%, respectively. Predicted probabilities of not yet completely recovered after more than a year since injury for these groups were 11.3%, 24.4%, and 37.6%, respectively. CONCLUSION: These results demonstrate significant differences in children with different forms of mTBI, and argue for further investigation of treatment plans individualized for each form of mTBI.